Manifestações folkcomunicacionais como propulsoras de empoderamento social no Ponto de Cultura Estrela de Ouro, em Aliança-PE - Martins, Júnia Mara Dias (2014)
Situated in rural area in the Aliança town, the Ranch Chã de Camará groups manifestations of popular culture, especially since 1966, the year in which the Master Batista founded the Maracatu Rural Estrela de Ouro. The history of the place is intertwined with the history of maracatu, of cavalo-marinho, of the sieves and the sugar economy, activities related to the Northern Forest Zone of Pernambuco. In 2004, the Estrela de Ouro became the first group in the Northeast as contemplated Point of Culture (PC). Point of Culture is the main action of Living Culture Program, which enables resources to cultural projects of nonprofits to develop ludic activities, artistic, sociocultural and digital inclusion for community. Every PC in its praxis, coexists with elements related to media – audiovisual production as purpose or means of recording and dissemination of cultural activities, ownership of communication tools and techniques for marginalized classes – which corroborates the research of point view of folkcommunication. Expansion and enhancement of access to means of production; cultural enjoyment and training; citizen action, communication, education and art; generation of employment and income; increasing identity and memory; it is believed that such questions, subsidized by folkcomunicacionais demonstrations, encourage individual and collective social empowerment in that community. This present thesis, enrolled in the Research Line Media and Everyday Life, examines therefore the manifestations folkcomunicacionais PC Estrela de Ouro. For this, identifies, delineates and describes this manifestations, with possible empowerment circumstances, still going by the description of their media activists. Theoretically, the case study is based on three pillars: 1. Folkcommunication, theory created by Luiz Beltrão 2. Social Empowerment, and 3. Point of Culture. The method adopted is ethnographic, using, among other instruments, unsystematic observation, photographic record and interviews. The approach is qualitative, exploratory and the analysis has interpretative character.